2017
DOI: 10.3389/fnins.2017.00495
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Modifies the Levels and Phosphorylation State of Tau Protein in Human Fibroblasts

Abstract: Since the tau protein is closely involved in the physiopathology of Alzheimer's disease (AD), studying its behavior in cellular models might lead to new insights on understanding this devastating disease at molecular levels. In the present study, primary cultures of human fibroblasts were established and used to determine the expression and localization of the tau protein in distinct phosphorylation states in both untransfected and tau gene-transfected cells subjected to oxidative stress. Higher immunopositivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…For p-tau (S199), a positive signal was detected in the cytosol and nucleus (suppl. Figure 3b,, online resource), with predominance in the nucleus, which is in-line with previous studies conducted in HeLa cells [36,73]. Such a signal was increased upon oxidative stress induction.…”
Section: Role Of Sfpq In Stress Responsesupporting
confidence: 91%
“…For p-tau (S199), a positive signal was detected in the cytosol and nucleus (suppl. Figure 3b,, online resource), with predominance in the nucleus, which is in-line with previous studies conducted in HeLa cells [36,73]. Such a signal was increased upon oxidative stress induction.…”
Section: Role Of Sfpq In Stress Responsesupporting
confidence: 91%
“…Specifically, we demonstrated that phosphorylated tau PHF-1 accumulates in the hippocampus of aged WT mice. Interestingly, it is reported that oxidative stress contributes to tau phosphorylation in PHF-1 and other epitopes in a mechanism that is still unknown 75 , 76 . It is reported that oxidative stress can induce tau phosphorylation through the activation of the glycogen synthase kinase-3β (GSK-3β) 77 and the activation of p38 MAPK 78 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Tau-depleted rat neurons exhibit a reduction of microtubule dynamics 38 , similar to what we observed for the mis-regulated microtubule array in both the cc1cc2 knockout 5 and the CC1-YYAA complemented mutant. Further functional and structural analogies between Tau and CC1 are reflected in the fact that both Tau and CC1 are relevant for the organism to function during stress conditions; CC1 promotes cellulose synthesis during salt stress 5 ; whereas, Tau has emerged as a key regulator of stress-induced brain pathology in mice and oxidative stress in cultured fibroblasts 39,40 .
Fig. 6Cartoon overview of the CC1-microtubule interaction and its similarity to Tau despite sequential differences.
…”
Section: Discussionmentioning
confidence: 99%